Increasing healthcare workers' uptake of seasonal influenza vaccination in a tertiary-care pediatric hospital in Greece with a low-cost, tailor-made, multifaceted strategy. Issue 29 (15th June 2020) - Kopsidas, Ioannis; Tsopela, Grammatiki-Christina; Maroudi-Manta, Stefania; Kourkouni, Eleni; Charalampopoulos, Dimitrios; Sirogianni, Alexandra; Collins, Madeline E.; Lourida, Athanasia; Kourlaba, Georgia; Zaoutis, Theoklis E.; Coffin, Susan E.
Highlights: We identified very low self-reported rates of SIV among HCWs. A simple low-cost tailor-made intervention strategy can increase SIV uptake among HCW. Stratifying according to vaccination history can reveal targets for improvement. Initiatives on improving vaccination uptake need to be ongoing. Abstract: Background: Healthcare workers' (HCW) seasonal influenza vaccination (SIV) is critical to prevent nosocomial influenza. However, HCW vaccination rates remain unacceptably low in many European institutions. A two-year three-step initiative was implemented at a tertiary-care pediatric hospital with 750 beds in Athens, Greece with the aim of increasing SIV among HCW. Methods: Α cross-sectional anonymous survey of HCWs was conducted during the 2015–16 influenza season with the aim to evaluate attitudes, knowledge, and specific barriers and facilitators for SIV. Stratified analysis was used to identify factors associated with no prior history of influenza vaccination. Multifaceted interventions were implemented in the 2016–2017 season. These included 1) education around influenza disease and SIV, and 2) communication of availability and opportunity (time and place) of SIV. Interventions were designed to target HCWs with the lowest SIV rates in the previous three years. Results: We achieved a 67% response rate, with 363 respondents (106 doctors, 145 nurses, 101 other hospital staff; 11 did not provide their profession). Most (64%) had not been vaccinated in the previous three years; only 14% received the vaccine annually. Non-vaccination rates were significantly higher among nurses (76%) and cleaning and food-service workers (73%) compared to doctors (40%) (P < 0.001). Protection of self, family, patients and colleagues were the most common motivations. Concerns about the safety and effectiveness of the vaccine, the belief that one does not belong to a high-risk group were the most common barriers. The interventions led to an increase in SIV uptake by the HCWs in the hospital, from 19% to 31%. Conclusions: In a country with very low reported rates of vaccination among HCWs, a simple, low-cost, tailor-made intervention strategy can lead to an increase in SIV uptake. Stratifying data according to vaccination history may reveal a diversity of targets for improvement that might otherwise be missed.